Understanding and Preventing Corruption - Graycar, A. author. aut Link
X, 161 p.
Keywords: Graycar and Prenzler present a readily accessible guide to the issues of public and private sector corruption, outlining the nature and dimensions of corruption problems in a variety of settings across the world, and providing a set of practical strategies to prevent corruption that also facilitate economic growth and development.